1998
DOI: 10.1002/(sici)1521-3951(199812)210:2<689::aid-pssb689>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Binding Energy and Structure of Localized Biexcitons in Quantum Wells

Abstract: A variational calculation of the ground state energy of a biexciton in a GaAs/AlGaAs quantum well is presented. The well width fluctuations leading to trapping of the biexcitons are modeled by a parabolic potential. The results obtained for different well widths are compared with recent experimental data.Good agreement is obtained both for the biexciton binding energy and for the Haynes factor. We find that the structure of a biexciton is similar to the one of the H 2 molecule.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…However, later experimental studies have reported substantial larger values for the binding energy [3][4][5][6][7] as compared to the early experiments. Moreover, later theories [13,14], while in agreement with each other, found a significant discrepancy with the binding energy of the biexciton as obtained by Kleinman. This difference was explained by Denschlag and Baltz [14] who found a missing factor of two in Kleinman's calculations.…”
Section: Introductionsupporting
confidence: 88%
“…However, later experimental studies have reported substantial larger values for the binding energy [3][4][5][6][7] as compared to the early experiments. Moreover, later theories [13,14], while in agreement with each other, found a significant discrepancy with the binding energy of the biexciton as obtained by Kleinman. This difference was explained by Denschlag and Baltz [14] who found a missing factor of two in Kleinman's calculations.…”
Section: Introductionsupporting
confidence: 88%
“…We believe that this discrepancy is a consequence of the increased localization of the exciton and trion with decreasing well width. A similar conclusion was also reached recently for biexcitons 23,17 . For CdTe-and ZnSe-based quantum wells the polaron effect, which was not included in our approach, is expected to lead to a substantial shift (∼ 1 meV) of the binding energy to larger values.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the conduction band non-parabolicity would increase the binding energy only slightly. We believe that the increased discrepancy between theory and experiment with decreasing well width is a consequence of the localization of the trion due to the presence of quantum well width fluctuations, as was also found for biexcitons 17,23 . This is consistent with the fact that for L=300Å our result agrees with the experiments and that the effect of the quantum well width modulation on the localization of the exciton and the trion increases with decreasing well width.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…a bound state of two excitons in GaAs quantum wells [1], their optical properties and dynamics have been intensively studied with the help of four-wave mixing [2][3][4][5][6][7][8][9], photoluminescence [1,7,[10][11][12], and differential absorption [5,13]. The measured biexciton binding energy, 0.2-0.3 of the exciton binding energy [1-3, 7, 8], appeared to be in good agreement with the theoretical value calculated with variational method [14][15][16][17], and geometric configuration approach [18,19].…”
mentioning
confidence: 56%
“…Second, we show that the simplest way to study biexcitons is to use the Hamiltonian of interacting excitons [23,24] that reduces a four-particle problem of two electrons and two holes to a problem of two excitons. The physical basis for this approach is the well-established experimental fact [1-3, 7, 8] supported by theoretical calculations [14][15][16][17][18][19] that the biexciton binding energy bx is a few times smaller than the exciton binding energy b . This small parameter allows us also to give a reasonable estimate for the biexciton binding energy.…”
mentioning
confidence: 99%